“Ejes de tratamiento del sistema nacional de rehabilitacion social y su incidencia en la obtecion del beneficio penitenciario de regimen semiabierto otorgado a las personas privadas de la libertad, durante el periodo comprendido de marzo a septiembre de 2016 en la unidad judicial penal con sede en el canton Riobamba” - Ortiz Machado, Susan Marianela (2017)
The Chapter I contains the referential framework in which is evidenced the problem statement, the justification and the subject objectives of the research are specified. As a general objective, it is proposed to describe how the treatment axes affect the obtaining of the penitentiary benefit of the semi-open regime in the National System of Social Rehabilitation, in the period from March to September 2016, in the Criminal Judicial Unit, placed in Riobamba city. The specific objectives that will materialize the general objective are: to determine throughout a critical analysis the axes of treatment of the National System of Social Rehabilitation, analyze the requirements that a deprived person of liberty must have in order to adopt the penitentiary benefit and analyze the penitentiary benefits of the semi¬open regime in the social and labor environment. In the Chapter II is stipulated the theoretical framework structured by sub-themes that cover the legal support for the development of the research. The first sub-theme is the state of the art that is based on collecting research papers related to the theme, the second sub-theme is subdivided into four units known as theoretical aspects that contains the thematical subject of the present study. In the First Unit it is studied the axes of treatment of the National System of Social Rehabilitation that are labor; Education, culture and sport, health; Familiar-social bonding and reintegration. The Second Unit covers what the semi-open regime is, the requirements required by law for a person deprived of liberty to have access to this penitentiary benefit and how the audience takes place. In the Third Unit is analyzed the penitentiary benefits of the semi-open regime in the social and labor environment in order to determine how the deprived of liberty people who were granted the change from closed regime to semi-open regime were treated by society at the moment to be reinserted and if